Financial Feasibility Study of Crystalline Xylose - Yudiastuti, Silvia Oktavia Nur; Dewi, Syahra Nakita; Handayani, Wiwik; Brilliantina, Aulia; Sari, Elok Kurnia Novita; Wijaya, Rizza; Slamet, Ahmad Haris Hasanuddin (P3M Politeknik Negeri Jember, 2024)
Xylose is a sugar obtained from breaking down hemicellulose. It is a polysaccharide found in the cellulose fibers of plant cell walls. One example of a plant containing hemicellulose is coffee, especially its waste called Coffee Cherry Processing Waste (CCPW). Its process's 10 L capacity production design was carried out to establish its mini factory. The financial feasibility study of each processing unit was designed. The research method used was quantitative methods. Apart from that, the approach used in this research is descriptive. The test results show that the crystalline xylose sugar processing unit is feasible to develop because the calculation results of the financial feasibility criteria are met with NPV > 0, B/C > 1, IRR 51%, PBP for two months < 5 years, which means the business owner could have returned his capital before the project period ends and BEP Q of IDR 15,565,013.54 while BEP Rp IDR 22,002479.88 was declared feasible because the BEP value was lower than the net income from xylose crystal sugar.